Recent advances in the pathogenesis and treatment of paroxysmal nocturnal hemoglobinuria - Luzzatto, Lucio (F1000Res, 2016)
Paroxysmal nocturnal hemoglobinuria (PNH) is a very rare disease that has been investigated for over one century and has revealed unique aspects of the pathogenesis and pathophysiology of a hemolytic anemia. PNH results from expansion of a clone of hematopoietic cells that, as a consequence of an inactivating mutation of the X-linked gene PIG-A, are deficient in glycosylphosphatidylinositol (GPI)-linked proteins: since these include the surface membrane complement-regulatory proteins CD55 and CD59, the red cells arising from this clone are exquisitely sensitive to lysis by activated complement. Until a decade ago, the treatment options for PNH were either supportive treatment – often including blood transfusion, anti-thrombosis prophylaxis, and sometimes thrombolytic therapy – or allogeneic bone marrow transplantation. Since 2007, PNH has received renewed and much wider attention because a new form of treatment has become available, namely complement blockade through the anti-C5 monoclonal antibody eculizumab. This brief review focuses on two specific aspects of PNH: (1) response to eculizumab, variability of response, and how this new agent has impacted favorably on the outlook and on the quality of life of patients; and (2) with respect to pathogenesis, new evidence supports the notion that expansion of the PNH clone results from T-cell-mediated auto-immune damage to hematopoietic stem cells, with the GPI molecule as target. Indeed, GPI-specific CD8+ T cells – which have been identified in PNH patients – would spare selectively GPI-negative stem cells, thus enabling them to re-populate the marrow of a patient who would otherwise have aplastic anemia.